PLAT LANTAI PRACETAK DENGAN BETON RINGAN - Pratikto Pratikto; Jessica Sagita; Nanda Mustaqim (Politeknik Negeri Jakarta, 2016)
ABSTRACT Installation of floor plate for ordinary terraced house with a conventional method or using Hebel relatively heavy and expensive. In addition, the size of a large hebel an obstacle to mobilization to the work site. This study aims to create a floor plate made of segments. To make it easier to carry, the segment of the floor plate is made using molds that can be assembled in the field to one lane and given reinforcement. Segment of the floor plate is made using lightweight concrete using a pumice stone with dimensions of 25x12x20 cm. The method used is a method in laboratory experiments conducted with a mix design that refers to ACI. Mixture contained in lightweight concrete is Sand: Cement: Pumice: superplasticizer. Sika ViscoCrete 1003 is used to reduce the water content of the concrete so that the weight becomes light. From the test results obtained by the heavy plate segment average floor of 7.47 kg with a compressive strength of 20.61 MPa, a tensile strength divided by 1.2 MPa, flexural strength of 1.63 MPa, and the resulting deflection with maximum compressive strength is 4.01 mm. Keywords : floor plate, segment, lightweight concrete ABSTRAK Pemasangan plat lantai untuk rumah bertingkat biasa dengan metode konvensional ataupun menggunakan hebel yang relative berat dan mahal. Selain itu, dengan ukuran hebel yang besar menjadi kendala untuk mobilisasi ke lokasi pekerjaan. Penelitian ini bertujuan membuat plat lantai yang dibuat dari segmen. Agar mudah dibawa, segmen plat lantai dibuat menggunakan cetakan yang dapat dirakit di lapangan menjadi satu jalur dan diberi tulangan. Segmen plat lantai dibuat menggunakan beton ringan yang menggunakan batu apung dengan dimensi 25x12x20 cm. Metode yang digunakan adalah metode eksperimen yang dilakukan di laboraturium dengan rancang campuran yang mengacu kepada ACI. Campuran yang terdapat didalam beton ringan adalah Pasir : Semen : Batu Apung : Superplasticizer. Sika ViscoCrete-1003 digunakan untuk mengurangi air sehingga bobot isi beton menjadi ringan. Dari hasil pengujian diperoleh berat segmen plat lantai rata-rata 7,47 kg dengan kuat tekan sebesar 20,61 Mpa, kuat tarik belah sebesar 1,2 Mpa, kuat lentur sebesar 1,63 Mpa, dan lendutan yang dihasilkan dengan kuat tekan maksimal adalah 4,01 mm. Kata kunci : plat lantai, segmen, beton ringan